The history of grinding - Lynch, A. J. (Society for Mining, Metallurgy, and Exploration, 2005)
An in-depth examination of the oldest engineering process, The History of Grinding begins at the start of agriculture and outlines how size reduction developed (without completely immersing the reader in technical detail). Chapters include size reduction from the stone age to the space age; the science and the scientists; hand stones, water wheels, windmills, and beyond; stamp mills and crushers; roller mills; tumbling mills; fine-grinding mills; classifiers; explosive rock breakage; and size reduction in the 21st century. Photos and illustrations gleaned from numerous sources, a glossary, ref.
Keywords: Grinding and polishing -- History.; elektronické knihy; electronic books